Yin and Yang of Biofilm Formation and Cyclic di-GMP Signaling of the Gastrointestinal Pathogen Salmonella enterica Serovar Typhimurium - Agaristi Lamprokostopoulou; Ute Römling (Karger Publishers, 2021)
Within the last 60 years, microbiological research has challenged many dogmas such as bacteria being unicellular microorganisms directed by nutrient sources; these investigations produced new dogmas such as cyclic diguanylate monophosphate (cyclic di-GMP) second messenger signaling as a ubiquitous regulator of the fundamental sessility/motility lifestyle switch on the single-cell level. Successive investigations have not yet challenged this view; however, the complexity of cyclic di-GMP as an intracellular bacterial signal, and, less explored, as an extracellular signaling molecule in combination with the conformational flexibility of the molecule, provides endless opportunities for cross-kingdom interactions. Cyclic di-GMP-directed microbial biofilms commonly stimulate the immune system on a lower level, whereas host-sensed cyclic di-GMP broadly stimulates the innate and adaptive immune responses. Furthermore, while the intracellular second messenger cyclic di-GMP signaling promotes bacterial biofilm formation and chronic infections, oppositely, Salmonella Typhimurium cellulose biofilm inside immune cells is not endorsed. These observations only touch on the complexity of the interaction of biofilm microbial cells with its host. In this review, we describe the Yin and Yang interactive concepts of biofilm formation and cyclic di-GMP signaling using S. Typhimurium as an example.